2019
DOI: 10.1017/s0021859619000352
|View full text |Cite
|
Sign up to set email alerts
|

Effect of royal jelly on milk composition and blood biochemical parameters in lactating ewes

Abstract: Use of antibiotics as feed additives has been reduced to avoid the hazard of drug residues, and consequently, the search for alternative natural additives has developed. Thus, the aim was to evaluate the influence of royal jelly (RJ) supplementation on milk composition, blood biochemical and antioxidant parameters of lactating ewes. Thirty-six Ossimi ewes were divided randomly into two groups (18 animals each). For a period of 4 weeks, the control group (CON) was fed a basal diet only, while the other group wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(55 reference statements)
0
1
1
Order By: Relevance
“…The protein and solid non fat content remained unaffected, nevertheless their values are within the range that is previously observed for the breed (Ivanova et al, 2011). Our results contradict to those of El-Tarabany et al (2019), who observed considerably higher fat and protein content of the milk in ewes supplemented with royal jelly. The density of the milk was higher in the supplemented group.…”
Section: Resultscontrasting
confidence: 75%
“…The protein and solid non fat content remained unaffected, nevertheless their values are within the range that is previously observed for the breed (Ivanova et al, 2011). Our results contradict to those of El-Tarabany et al (2019), who observed considerably higher fat and protein content of the milk in ewes supplemented with royal jelly. The density of the milk was higher in the supplemented group.…”
Section: Resultscontrasting
confidence: 75%
“…Bonomi and Bonomi (2004) found that the addition of royal jelly was able to induce a significant improvement of milk yield in dairy cattle. Also, El-Tarabany et al (2019) recorded that the ewes supplemented with RJ had higher in daily milk yield than untreated ewes. The results regarding to eCG effect on milk production in coincide with Rebollar et al (2008) reported that the eCG when administration at day 9 postpartum lead to decrease in PRL concentrations.…”
Section: Litter Size At Birth (After Lactation)mentioning
confidence: 96%